Pengembangan Modul Pembelajaran Matematika Berbasis Reading, Mind Mapping and Sharing dalam Meningkatkan Kemampuan Representasi Matematis Peserta Didik Kelas VII MTsN 5 Lima Puluh Kota - Ramadani Juliana; Elda Herlina (Edusainstika: Jurnal Pembelajaran MIPA, 2022)
This study aims to develop a valid and practical Reading, Mind Mapping and Sharing-based mathematics learning module so that it can be used in online learning. The fact on the ground is that the learning resources used only use the 2013 curriculum package, with an insufficient number of students. To overcome this, it is necessary to have additional learning resources that will guide students in learning so that they can develop students' mathematical abilities, especially representational abilities. This research uses development research method with three stages of development, namely 1) defining stage, 2) designing, and 3) developing. The research instruments used were validation sheets and student response questionnaires. While the data analysis technique used is the percentage of the results of the validation and practicality test. Based on the results of the study showed that the RMS-based module was valid and practical. The results of the validation obtained an assessment of 86% with a very valid category and the assessment of 33 grade VII students of MTsN 5 Lima Puluh Kota on the RMS-based module was categorized as practical with an average of 79.73%.